New food sources and production systems: a comparison of international regulations and China’s advancements in novel foods with synthetic biology - Xin Liu; Di Wu; Yi Shao; Yongning Wu (Food Science and Human Wellness)
The global shift towards sustainable food systems has sparked innovations in food sources and production systems, including cell-based meat, plant-based food products, precision fermentation, and 3D food printing. These advancements pose regulatory challenges and opportunities, with China emerging as a critical player in adopting and regulating new food technologies. This review explores the international landscape of new food sources and production systems (NFPS), focusing on China’s role and regulatory approaches compared to global practices. Through this comparative analysis, we aim to contribute to the ongoing dialogue on food safety regulation, offering insights and recommendations for policymakers, industry stakeholders, and researchers engaged in the global food system’s evolution. This comprehensive overview underscores the dynamic nature of regulatory frameworks governing NFPS, highlighting the international efforts to ensure food safety, consumer protection, and the sustainable evolution of the food industry.